A framework for quantitative analysis of livestock systems using theoretical concepts of production ecology. (October 2015) - van der Linden, Aart; Oosting, Simon J.; van de Ven, Gerrie W.J.; de Boer, Imke J.M.; van Ittersum, Martin K.
Abstract: In crop science, widely used theoretical concepts of production ecology comprise a hierarchy in growth defining, limiting, and reducing factors, which determine corresponding potential, limited, and actual production levels. These concepts give insight in theoretically achievable production, yield gaps, and yield gap mitigation. Concepts of production ecology have been demonstrated to be applicable to livestock science, but so far they have not been used quantitatively for livestock production. This paper aims to define theoretical concepts of production ecology for livestock systems in more detail, to express livestock production in suitable units, and to provide a framework to analyse production levels for livestock systems and combined crop–livestock systems. Growth defining (genotype and climate), growth limiting (feed quality and quantity), and growth reducing factors (diseases and stress) in livestock production are described analogous to the growth factors in crop production. Management practices, such as housing, feeding, culling, and slaughter are specified. From the perspective of a livestock system, production is expressed per animal, per unit of animal body mass, and per unit of feed intake, whereas from the perspective of a combined crop–livestock system, production is recommended to be expressed in kg livestock product ha − 1  year − 1 . The quantitative framework is illustrated for Charolais cattle ( Bos taurus subsp.) in two beef production systems in France, differing in feeding strategies. System A produces heavier calves than system B, whereas cattle in system B are fed a higher fraction of concentrates in the diet compared with system A. Potential beef production was similar for systems A and B, and estimated to be 152 kg beef animal − 1  year − 1 and 251 g beef kg − 1  live weight year − 1, while there was a minor difference when expressed per unit of feed intake (54.5 vs 54.8 g beef kg − 1 DM). Actual production was lower for system A than for system B (24.9 vs 31.2 g beef kg − 1 DM). Potential production for combined crop–livestock systems was again similar for systems A and B (631 vs 634 kg beef ha − 1  year − 1 ), while actual production was much lower for system A than for system B (133 vs 180 kg beef ha − 1  year − 1 ). The yield gap for crop–livestock systems was 79% of potential production for system A and 72% for system B. We conclude that the framework is effective to reveal the scope to increase production and resource use efficiency in livestock production. Graphical abstract: Highlights: We define production ecological concepts for livestock production systems. We quantify potential and actual production of beef cattle for two farm types. Relative yield gaps were 54% and 43% for the livestock systems in the farm types. Relative yield gaps were 79% and 72% for the feed crop–livestock systems. Production ecological concepts were applied effectively to livestock production.